HLM, a TNM-like classification for heart failure, compared with other nosologies at 12 months follow-up. (25th November 2020) - Severino, P; Pucci, M; Mariani, M.V; D'Amato, A; Infusino, F; Birtolo, L.I; Morano, G; D'Ascenzo, F; Maestrini, V; Mancone, M; Fedele, F
Abstract: Background: Heart failure (HF) is the pandemic of the third millennium with the highest mortality among general population, while lung cancer is the second most common cause of death. As cancer, HF can affect close organs, as lungs, or can reach peripheral organs (kidney, liver, brain), leading to multi-organ dysfunction, like cancer metastasis. Purpose: We proposed a new staging system named HLM, analogous to TNM classification used in oncology, which refers to heart damage (H), lung involvement (L), and malfunction (M) of peripheral organs. The aim of this study is a comparison between HLM and NYHA, ACC/AHA and MAGGIC scores to assess the most accurate prognosis of HF patients in terms of rehospitalization for acute HF (AHF) or major adverse cardiac and cerebrovascular events (MACCE), and cardiac death. Methods: We performed a single-center observational study of HF patients. All parameters for heart, lungs and peripheral organs function were examined. Each patient was classified according to HLM, NYHA, ACC/AHA and MAGGIC score at the entrance and at the discharge. Rehospitalization for MACCE or AHF and cardiac death were checked at 12 months follow up. Results: We enrolled 2054 patients: 68.5% males, 31.3% females, mean age 70.18±7.48 years. Among them, overall survival curves regarding rehospitalization for MACCE, AHF and cardiac death at 12 months, show that HLM classification is as valid as the others (p<0.001). In particular, the area under the ROC curve (AUC) is greater for HLM than NYHA, ACC/AHA and MAGGIC score in terms rehospitalisation for MACCE (HLM=0.687; NYHA=0.642; ACC/AHA=0.604; MAGGIC=0.657) or AHF (HLM=0.662; NYHA=0.652; ACC/AHA=0.604; MAGGIC=0.662) and cardiac death (HLM=0.783; NYHA=0.712; ACC/AHA=0.623; MAGGIC=0.737). Conclusion(s): According to our results, HLM classification has greater prognostic power compared to other nosologies in terms of rehospitalization for MACCE, AHF and cardiac death for HF patients, thanks to a more accurate evaluation of the systemic impact of heart failure. Such a multivariable, holistic approach should be used in HF patients, rather than a "cardiocentric" approach, in order to address the pathophysiological mechanisms underlining heart abnormalities, improving clinical management and costs. Funding Acknowledgement: Type of funding source: None